2016
DOI: 10.1111/acps.12587
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met polymorphism and peripheral protein levels in pediatric bipolar disorder and attention‐deficit/hyperactivity disorder

Abstract: Although the Val66Met polymorphism at the BDNF gene does not seem to play a significant role in children and adolescents with BD or ADHD, BDNF serum levels deserve further attention in future research on neurobiological aspects of BD and ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…28,29 Although international differences in BD are less well studied in youth as compared to adults, there now are PBD data from multiple countries including Australia/New Zealand, Brazil, China, France, India, Italy, South Korea, Spain, the Netherlands, Turkey, and the UK. 30 In addition to the epidemiologic studies reviewed above, international BD data now include phenomenological, 19,3133 comorbidity, 19,34 longitudinal, 35,36 treatment, 37,38 neuroimaging and biomarker, 3941 and high-risk studies. 42,43 Numerous commentaries discuss purported international differences in the prevalence of PBD, which may be attributable to including more subtypes, 1 differences in the interview method, 44 training, 23,45 or the type of sample studied (predominantly manic, depressive, treatment-seeking or registry), or a combination of these.…”
Section: | International Findingsmentioning
confidence: 99%
“…28,29 Although international differences in BD are less well studied in youth as compared to adults, there now are PBD data from multiple countries including Australia/New Zealand, Brazil, China, France, India, Italy, South Korea, Spain, the Netherlands, Turkey, and the UK. 30 In addition to the epidemiologic studies reviewed above, international BD data now include phenomenological, 19,3133 comorbidity, 19,34 longitudinal, 35,36 treatment, 37,38 neuroimaging and biomarker, 3941 and high-risk studies. 42,43 Numerous commentaries discuss purported international differences in the prevalence of PBD, which may be attributable to including more subtypes, 1 differences in the interview method, 44 training, 23,45 or the type of sample studied (predominantly manic, depressive, treatment-seeking or registry), or a combination of these.…”
Section: | International Findingsmentioning
confidence: 99%
“…Of all the neurotrophic proteins we evaluated, BDNF appears to have been the one most often considered a candidate for a role in the occurrence of ADHD (Shim et al, 2008; Scassellati et al, 2014; Liu et al, 2015). And yet, the data are conflicting, with some studies reporting higher peripheral concentrations (Yeom et al, 2016), and others failing to find any association (Scassellati et al, 2014; Zeni et al, 2016). Gene studies have also failed to produce a coherent relationship between BDNF-related genes and the risk of ADHD (Cho et al, 2010; Zeni et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…And yet, the data are conflicting, with some studies reporting higher peripheral concentrations (Yeom et al, 2016), and others failing to find any association (Scassellati et al, 2014; Zeni et al, 2016). Gene studies have also failed to produce a coherent relationship between BDNF-related genes and the risk of ADHD (Cho et al, 2010; Zeni et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that this correlation did not maintain statistical significance after adjusting for multiple comparisons [ 126 ]. In contrast, Zeni et al (2016a) found no significant association between the rs6265 polymorphism and BDNF serum levels in children and adolescents with BD comorbid with attention-deficit/hyperactivity disorder (ADHD) [ 127 ]. Moreover, Kenna et al (2014) did not see any difference in val66met polymorphism and plasma BDNF concentrations between women with BD and healthy controls [ 128 ].…”
Section: Polymorphismmentioning
confidence: 99%